EVALUATION OF INTENSIFICATION IMPLEMENTATION OF SOLAR ENERGY by CONSTRUCTING COGNITIVE MAPS - Казак, В.; Ковбій, К.; Панченко, Я. (Science-based technologies, 2011)
The  opportunities  of  intensifying  the  intensification  of  solar energy  by  constructing  cognitive  maps  were evaluated  in  the article.  Analyzing  received  cognitive  map,  you  can  draw conclusions  concerning  the relationship of factors affecting the implementation of the intensification of solar energy in the Odessa region, to predict the effects of changing one or more factors.